S338 Phosphorylation of Raf-1 Is Independent of Phosphatidylinositol 3-Kinase and Pak3 - Chiloeches, Antonio (American Society for Microbiology, 2001)
The Raf-1 serine/threonine protein kinase requires phosphorylation of the serine at position 338 (S338) for activation. Ras is required to recruit Raf-1 to the plasma membrane, which is where S338 phosphorylation occurs. The recent suggestion that Pak3 could stimulate Raf-1 activity by directly phosphorylating S338 through a Ras/phosphatidylinositol 3-kinase (Pl3-K)/-Cdc42-dependent pathway has attracted much attention. Using a phospho-specific antibody to S338, we have reexamined this model. Using LY294002 and wortmannin, inhibitors of Pl3-K, we find that growth factor-mediated S338 phosphorylation still occurs, even when Pl3-K activity is completely blocked. Although high concentrations of LY294002 and wortmannin did suppress S338 phosphorylation, they also suppressed Ras activation. Additionally, we show that Pak3 is not activated under conditions where S338 is phosphorylated, but when Pak3 is strongly activated, by coexpression with V12Cdc42 or by mutations that make it independent of Cdc42, it did stimulate S338 phosphorylation. However, this occurred in the cytosol and did not stimulate Raf-1 kinase activity. The inability of Pak3 to activate Raf-1 was not due to an inability to stimulate phosphorylation of the tyrosine at position 341 but may be due to its inability to recruit Raf-1 to the plasma membrane. Taken together, our data show that growth factor-stimulated Raf-1 activity is independent of Pl3-K activity and argue against Pak3 being a physiological mediator of S338 phosphorylation in growth factor-stimulated cells.